Casein kinase II phosphorylation of cyclin F at serine 621 regulates the Lys48-ubiquitylation E3 ligase activity of the SCF(cyclin F) complex. Issue 10 (11th October 2017) - Lee, Albert; Rayner, Stephanie L.; De Luca, Alana; Gwee, Serene S. L.; Morsch, Marco; Sundaramoorthy, Vinod; Shahheydari, Hamideh; Ragagnin, Audrey; Shi, Bingyang; Yang, Shu; Williams, Kelly L.; Don, Emily K.; et al.
Abstract : Abstract : Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disorder that is characterized by progressive weakness, paralysis and muscle loss often resulting in patient death within 3–5 years of diagnosis. Recently, we identified disease-linked mutations in the CCNF gene, which encodes the cyclin F protein, in cohorts of patients with familial and sporadic ALS and frontotemporal dementia (FTD) (Williams KL et al . 2016 Nat. Commun. 7, 11253. (doi:10.1038/ncomms11253 )). Cyclin F is a part of a Skp1-Cul-F-box (SCF) E3 ubiquitin-protein ligase complex and is responsible for ubiquitylating proteins for degradation by the proteasome. In this study, we investigated the phosphorylation status of cyclin F and the effect of the serine to glycine substitution at site 621 (S621G) on E3 ligase activity. This specific mutation (S621G) was found in a multi-generational Australian family with ALS/FTD. We identified seven phosphorylation sites on cyclin F, of which five are newly reported including Ser621. These phosphorylation sites were mostly identified within the PEST (proline, glutamic acid, serine and threonine) sequence located at the C-terminus of cyclin F. Additionally, we determined that casein kinase II (CK2) can phosphorylate Ser621 and thereby regulate the E3 ligase activity of the SCF (cyclin F) complex. Furthermore, the S621G mutation in cyclin F prevents phosphorylation by CK2 and confers elevated Lys48-ubiquitylation activity, a hallmark of ALS/FTD pathology. These findings highlight the importance of phosphorylation in regulating the activity of the SCF (cyclin F) E3 ligase complex that can affect downstream processes and may lead to defective motor neuron development, neuron degeneration and ultimately ALS and FTD.